PGLDA: enhancing the precision of topic modelling using poisson gamma (PG) and latent dirichlet allocation (LDA) for text information retrieval - Bakari, Ibrahim Bala (2021)
The Poisson document length distribution has been used extensively in the past for modeling topics with the expectation that its effect will disintegrate at the end of the model definition. This procedure often leads to down Playing word correlation with topics and reducing retrieved documents' precision or accuracy. The existing document model, such as the Latent Dirichlet Allocation (LDA) model, does not accommodate words' semantic representation. Therefore, in this thesis, the PoissonGamma